Control of residual amounts of copper-containing pesticides in plant products - N. E. Fedorova; M. V. Egorova; A. S. Rodionov; M. S. Grechina (Овощи России, 2020)
Relevance and methods. Methodological approaches to assessing the residual amounts of copper-containing pesticides in plant products against the background of natural copper content are presented. The conditions for obtaining reliable results when conducting a hygienic assessment of the content of residual amounts of the active substance are determined. The developed scheme for determining the residual amounts of copper-containing pesticides includes the homogenization of the analyzed material by shredding with dry ice and microwave mineralization of samples with subsequent flameless atomic absorption determination of copper.Results. Data on the levels of natural copper content in samples of potatoes, onions, cucumbers, tomatoes and grapes of various varieties and growing areas are presented. The possibility of applying the developed approaches to study the dynamics of accumulation of active substances during the growing season is shown.